Effect of processed sweet lupin (Lupinus angustifolius) grain supplementation on growth performance and socioeconomic feasibility of Doyogena sheep in Ethiopia - Tilaye, Habite; Asmare, Bimrew; Meheret, Fentahun; Bezabih, Melkamu; Wamatu, Jane (Wiley, 2022)
Background